Dapsone Alters Phenotypical and Functional Properties of Human Neutrophils In Vitro - Sara Rakočević; Vanja Mališ; Ljiljana Kozić; Anđela Dubovina; Marija Drakul; Dejan Bokonjić; Miodrag Čolić; Dušan Mihajlović (Molecules)
Dapsone is a sulfone used in treating inflammatory skin conditions. Despite its widespread dermatological use, the pharmacological actions of dapsone remain poorly understood. Here, we examined how different aspects of neutrophil functions are affected by dapsone. Peripheral blood neutrophils from healthy donors were stimulated with phorbol-12-myristate-13-acetate (PMA), N-formyl-L-methionyl-L-leucyl-L-phenylalanine (fMLP), or calcium ionophore (CaI) or primed with cytokines prior to stimulation, in the presence of different concentrations of dapsone (from 10 to 50 µg/mL), followed by analyses of their survival, phenotype, and functional properties. We found that dapsone at the concentration of 50 μg/mL induced a significant neutrophil apoptotic rate during 6 h and 18 h, while other concentrations were well tolerated compared to control non-treated cells. However, dapsone significantly decreased the induced oxidative burst of neutrophils at all non-cytotoxic concentrations. Additionally, dapsone showed a dose-dependent suppression of NETosis in activated neutrophils. The production of IL-8 by dapsone-treated neutrophils was decreased under both stimulated (fMLP) and primed (TNF-α/fMLP) conditions. Moreover, dapsone inhibited the expression of CD11b/CD18, CD66, and CD89 and reversed or significantly mitigated the downregulation of CD16, CD32, CD181, CD88, and CD62L on neutrophils after priming and fMLP stimulation. In conclusion, our results indicate the complexity of dapsone actions on neutrophil functions, extending previous knowledge on the suppression of oxidative burst and IL-8 production upon neutrophils’ activation. Suppressed NETosis and modulation of marker expression associated with different neutrophil functions under inflammatory conditions are new findings, not recognized previously.